2012
DOI: 10.1111/emr.12002
|View full text |Cite
|
Sign up to set email alerts
|

Eastern Suburbs Banksia Scrub: Rescuing an endangered ecological community

Abstract: On‐ground works prove an important mechanism for gaining knowledge about this near‐extinct ecological community, providing new insights into ways to manage and restore it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 7 publications
(9 reference statements)
0
12
0
Order By: Relevance
“…Ex situ conservation measures, in which parts of the population are placed in a new location, could preserve the species in areas of low habitat suitability (Frankham 2010 ; Gong et al 2010 ; Vranckx et al 2012 ) and could be used to establish future environments while retaining existing genetic diversity. Although genetic diversity cannot be maintained in these areas due to the impact of climate change, it is important to allow them to shift away from their native range, that is, unsuitable habitats, to alternative, appropriate environments for culturing, in other words, ex situ conservation (Perkins et al 2012 ; Cires et al 2013 ; Dubey et al 2013 ). In situ conservation measures, which include nature reserves and various types of scenic areas, can be used to maintain the evolution and reproductive potential of the ecological system (Jiang et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ex situ conservation measures, in which parts of the population are placed in a new location, could preserve the species in areas of low habitat suitability (Frankham 2010 ; Gong et al 2010 ; Vranckx et al 2012 ) and could be used to establish future environments while retaining existing genetic diversity. Although genetic diversity cannot be maintained in these areas due to the impact of climate change, it is important to allow them to shift away from their native range, that is, unsuitable habitats, to alternative, appropriate environments for culturing, in other words, ex situ conservation (Perkins et al 2012 ; Cires et al 2013 ; Dubey et al 2013 ). In situ conservation measures, which include nature reserves and various types of scenic areas, can be used to maintain the evolution and reproductive potential of the ecological system (Jiang et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments with small fires at the York Rd ESBS community are yet to demonstrate statistically significant increases (Perkins et al . ). Evidence from our burn experiments suggests the fire can produce a greater increase in species richness in degraded scrub than in nondegraded scrub even in the short term, but that a full response from all species present in the soil may take years and a range of treatments.…”
Section: Progress and Future Directionsmentioning
confidence: 97%
“…The ESBS Recovery Plan (NSW Department of Environment & Conservation 2004) identified a need for public land managers of sites with ESBS to undertake management actions to protect, repair and expand remaining patches of this ecosystem. Potential for restoration after domination by Coastal Teatree is evidenced by encouraging results of restoration works at other ESBS sites (Perkins et al 2012). Works at the York Road ESBS site in particular have shown that carefully designed interventions can lead to incremental increases in plant diversity over periods of 5 years or more (including recovery of Characteristic ESBS species) although sites of longer degradation are slower to show increases in species (Parsons Brinkerhoff 2012;Perkins et al 2012).…”
Section: Conditionmentioning
confidence: 99%
See 2 more Smart Citations